Chromatographic purification strategies for recombinant human transferrin from spodoptera frugiperda - Wee, Chen Chen (2008)
Insect cell-baculovirus system is an excellent artificial system for the production of recombinant glycoprotein despite its glycosylation deficiencies. In this study, laboratory scale production of recombinant human transferrin (rhTf) from insect cell-BEVS was conducted and chromatographic purification strategies were employed to obtain rhTf in high yield and high recovery. Research was started with the amplification of recombinant baculovirus, using low multiplicity of infection (MOI). Virus stock in a 1.2 x 109 pfu/ml infected suspension culture of Spodoptera frugiperda (Sf9) at 15 MOI had produced 31Âµg/ml of rhTf. To purify the rhTf, hydrophobic interaction chromatography, dialysis and ion exchange chromatography were performed. For hydrophobic interaction chromatography, elution strategy, flowrate and rhTf loading capacity of phenyl sepharose were optimized. By loading 38Âµg rhTf/ml of gel, employing step elution with 50% 1.2M (NH4)2SO4/0.4M Na3C6H5O7, pH6 (buffer A) and 25% buffer A and flowrate at 1ml/min, 74.6% of rhTf had been recovered from phenyl sepharose. For ion exchange chromatography, batch purification in reduced size was used to select suitable anion exchange matrix, suitable pH of equilibration buffer and concentration of equilibration buffer. 20mM Tris/HCl buffer, pH8.5 and gradient elution with the increase of of 5mM NaCl/CV succeeded in giving pure rhTf with 52.5% recovery from Q-sepharose. The overall recovery of pure rhTf was 34% with 200 purification fold. A brief glycan characterization of the recovered pure rhTf was performed for a better understanding of the glycosylation feature of this protein expressed using optimized medium from BEVS. The carbohydrate component of the purified rhTf was determined. The purified rhTf was hydrolyzed and the release sugar was labeled with 1-Phenyl-3- Methyl-5-Pyrazolone (PMP) before analysis with High performance Liquid Chromatography (HPLC). The molar fractions of Man, GlcNAc and Gal of rhTf were 3.78, 1.69 and 0.93, respectively.